Surfactant protein B deficiency and gene mutations for neonatal respiratory distress syndrome in China Han ethnic population - Yin, Xiaojuan (e-Century Publishing Corporation, 2013)
Objective: To determine whether the SP-B deficiency and gene mutations in exon 4 is associated with neonatal RDS in China Han ethnic population. Methods: The study population consisted of 40 neonates with RDS and 40 neonates with other diseases as control in China Han ethnic population. We Compared SP-B expression in lung tissue and bronchoalveolar lavage fluid with immunoblotting, and analyzed mutations in the SP-B gene with polymerase chain reaction (PCR) and gene sequencing. Results: In RDS group, low mature Surfactant protein B was found in both lung tissue and bronchoalveolar lavage fluid in 8 neonates. In control group, only 4 neonates with low mature Surfactant protein B in both lung tissue and bronchoalveolar lavage fluid. In RDS group, 20 neonates were found to have mutations in exon 4, 12 homozygous mutations with C/C genotype and 8 heterozygous mutations with C/T genotype in surfactant protein B gene+1580 polymorphism. There were 8 cases mutations in control group, 1 in C/C and 7 in C/T genotype. The frequency of homozygotes with C/C genotype was 0.3 and frequency of heterozygotes with C/T genotype was 0.02 in RDS group. In control group, frequency of homozygotes with C/C genotype was 0.025 and frequency of heterozygote with C/T genotype was 0.175. Conclusion: Low mature Surfactant protein B is associated with the pathogenesis of neonatal respiratory distress syndrome (RDS) in China Han ethnic population. Mutations in exon 4 of the surfactant protein B gene demonstrate an association between homozygous mutations with C/C genotype in SP-B gene and neonatal RDS.